2020
DOI: 10.1021/acsami.0c17046
|View full text |Cite
|
Sign up to set email alerts
|

One-Step and Low-Cost Designing of Two-Layered Active-Layer Superhydrophobic Silicalite-1/PDMS Membrane for Simultaneously Achieving Superior Bioethanol Pervaporation and Fouling/Biofouling Resistance

Abstract: Recently, the coupling of biofuel fermentation broths and pervaporation has been receiving increasing attention. Some challenges, such as the destructive effects of constituents of the real fermentation broth on the membrane performances, the lethal effects of the membrane surface chemical modifiers on the microorganisms, and being expensive, are against this concept. For the first time, a continuous study on the one-step and low-cost preparation of superhydrophobic membranes for bioethanol separation is made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 87 publications
(192 reference statements)
1
20
0
Order By: Relevance
“…where v d is the number of moles of the elastic network chains in 1 cm 3 , ρ is the density of the PDMS membrane, and M c is the mass of the PDMS sample containing 1 mol elastic molecular chains. 2.6.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…where v d is the number of moles of the elastic network chains in 1 cm 3 , ρ is the density of the PDMS membrane, and M c is the mass of the PDMS sample containing 1 mol elastic molecular chains. 2.6.…”
Section: Characterizationmentioning
confidence: 99%
“…Polydimethylsiloxane (PDMS) is a widely used polymer material for membrane fabrication, since it is easily fabricated, is chemically stable, and has a great affinity with organics as well as high hydrophobicity. The PDMS membrane can be applied for organic solvent recovery, , VOC removal, , and gas separation. , Besides, it has been reported that higher productivity and lower energy required can be achieved, if pervaporation separation by the PDMS membrane is coupled with ethanol fermentation for bioethanol in situ removal from the broth to eliminate ethanol inhibition. , In conventional methods for PDMS membrane fabrication, membrane thickness vs defects, or membrane flux vs selectivity, is always an irritating trade-off problem. Thus, optimizing the membrane thickness while limiting membrane defects to boost the separation performance is of great importance for developing PDMS membranes. In order to achieve this objective, the thin-film composite (TFC) membrane has been considered an alternative with a thinner thickness to get a higher membrane flux …”
Section: Introductionmentioning
confidence: 99%
“…24 Introducing superhydrophobicity into conductive fabrics is one of the effective ways to solve obstacles to their application. 5,25 A superhydrophobic surface usually refers to a material or object surface, which can make the water droplets falling on it present a surface with a water contact angle (WCA) 4 1501 and a sliding angle (SA) o 51. [26][27][28] Such materials are inspired by nature, such as lotus leaves, the feet of water striders, 29,30 butterfly wings, 31 taro leaves, 32 rose petals, 33,34 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Although hydrophobic non-porous polymeric membranes, such as polydimethylsiloxane (PDMS), et al, have excellent biobutanol/ water separation performance, it is still suffering from limited perm-selectivity. [9] In recent years, the incorporation of porous nanofiller with alcohol affinities such as silicalite-1, [10] ZSM-5 zeolite, [11] silica, [12] and metal-organic frameworks (MOFs) [13,14] into a polymer-based membrane has been considered as a promising strategy to address this issue.…”
Section: Introductionmentioning
confidence: 99%